2018
DOI: 10.1136/bcr-2017-223977
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric panniculitis: diagnostic precision

Abstract: A previously healthy 74-year-old woman was admitted with vespertine fever, tremors, shivers and loss of appetite within the previous month. Blood tests revealed an elevated C reactive protein serum level. Serologies for infection were negative. Blood cultures grew no organisms. Colonoscopy revealed normal findings. CT showed typical findings of mesenteric panniculitis with infiltration of mesenteric fat that was circumscribed by hyperattenuating capsule and contained enlarged homogenous lymph nodes. The histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In some cases, a histopathological analysis from the biopsy of the mesenteric tissue may reveal nonspecific signs of chronic inflammation. 17 The 3 stages that may co-exist in MP include 14 the following:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, a histopathological analysis from the biopsy of the mesenteric tissue may reveal nonspecific signs of chronic inflammation. 17 The 3 stages that may co-exist in MP include 14 the following:…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a histopathological analysis from the biopsy of the mesenteric tissue may reveal nonspecific signs of chronic inflammation. 17 The 3 stages that may co-exist in MP include 14 There is no consensus among physicians for the treatment of MP and therefore no specific treatment protocols exist. The choice of treatment is guided by symptomatology and is usually tailored to individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Coulier et al 5 reported that steroids resulted in rapid improvement in joint symptoms, abdominal pain, and inflammatory syndrome of a patient who was diagnosed with MP and had an acute gastrointestinal attack of adult-onset Henoch-Sch€ onlein purpura. Sousa et al 11 reported that they used prednisolone in the first month, and replaced it with azathioprine after 12 months of therapy to cure a 74-year-old woman with MP. However, long-term follow-up of MP is required to observe posttreatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Sousa et al. 11 reported that they used prednisolone in the first month, and replaced it with azathioprine after 12 months of therapy to cure a 74-year-old woman with MP. However, long-term follow-up of MP is required to observe posttreatment outcomes.…”
Section: Discussionmentioning
confidence: 99%